Characteristics of the diet of the western barn owl and the little owl in the Zakarpattia Oblast (Ukraine) - Mykhailo Drebet; Leonid Pokrytiuk (Theriologia Ukrainica)
The article presents the results of an analysis of approximately 150 pellets (containing 178 food items) of the Little Owl (Athene noctua) and about 300 pellets (containing 1,268 food items) of the Barn Owl (Tyto alba) collected in the Berehove District, Zakarpattia Region, during 2006–2008. The analysis of owl pellets is a highly effective method for studying the composition of faunal communities and the structure of prey species assemblages. Pellet analysis serves as a reliable tool for monitoring programs and for identifying indicator species of small mammals. Among owl species common in Europe, the populations of the Barn Owl and, especially, the Little Owl are steadily declining, primarily due to ongoing urbanization, which increases bird mortality. The Barn Owl, in particular, suffers from the modernization and reconstruction of buildings, leading to the loss of traditional nesting sites. Small mammals constitute the primary prey of both owl species, comprising 99.8% of the Barn Owl’s diet and 90.4% of the Little Owl’s diet. The trophic niche breadth of the Barn Owl, based on Simpson’s index, is twice as wide as that of the Little Owl (5.2 vs. 2.0, respectively). The overlap of trophic niches between these predators, measured using Pianka’s index, is 70.5%. The greatest similarity in prey usage is observed in the consumption of secondary and supplementary food components (91.7–99.3%), whereas similarity in the use of the primary prey species (Microtus arvalis) is lower, at 71.1%. During periods of environmental degradation and reduced abundance of the primary prey, trophic niche overlap increases due to shared consumption of secondary and supplementary prey species. The Little Owl expands its trophic niche by including vertebrates from various taxonomic classes (birds, reptiles, amphibians, and fish), while the Barn Owl broadens its niche by incorporating a greater diversity of small mammal species. This niche expansion reduces interspecific competition. Despite the overall similarity in diet composition, the trophic niches of the Barn Owl and Little Owl in Zakarpattia do not completely overlap. The similarity in the use of the primary prey is approximately 70%, which facilitates their coexistence.